New life to Italian university anatomical collections: desire to give value and open museological issues. Cases compared - Monza, Francesca; Cusella, Gabriella; Ballestriero, Roberta; Zanatta, Alberto (Polish Journal of Pathology, 2019)
The anatomical museums are one of the most difficult categories of museums to deal with because the issues addressed and the stored materials are complex to communicate and often not suitable for all audiences. The history of medicine teaches us that the knowledge of our body is a fascinating topic that continues to be the subject of study and research. The Italian anatomical museums are mostly university property, often closed and with specimens in urgent need of restoration. Their rooms still house important collections of human biological samples, dry or in liquid, collected between the eighteenth and twentieth century: a historical heritage that testifies to the evolution of medical science and provides a searchable archive of biological and genetic data. The curator of such a museum must confront many issues – museological, legislative and ethical – many of which are unclear and incomplete. This article provides an overview of museological issues in the anatomical area in order to offer ideas and visions, from a comparison of three different examples: the Museum of Human Anatomy of the University of Pavia, the Museum of Pathological Anatomy at the University of Padua and the Gordon Museum of Pathology in London.